2004
DOI: 10.1161/01.str.0000115751.45473.48
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Smoking and the Risk of Subarachnoid Hemorrhage

Abstract: Background and Purpose-This study was undertaken to better clarify the risks associated with cigarette smoking and subarachnoid hemorrhage (SAH). Methods-The study included 432 incident cases of SAH frequency matched to 473 community SAH-free controls to determine dose-dependent associations of active and passive smoking (at home) and smoking cessation with SAH. Results-Compared with never smokers not exposed to passive smoking, the adjusted odds ratio for SAH among current smokers was 5.0 (95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…Most longitudinal studies were initiated in the 1970s and were restricted to the US, Japanese, UK, Korean, and Finnish populations. Of the 23 case-control studies, 10 (63% of SAH cases) [12][13][14][15][16][17][18][19][20][21] were population based and 13 hospital based, [22][23][24][25][26][27][28][29][30][31][32][33][34] covering a variety of populations: American (United States), Latin American (Chile, Colombia, Mexico, Brazil, and Jamaica), European (Norway, Germany, Hungary, Portugal, Denmark, Yugoslavia, Slovenia, Finland, and the United Kingdom), African (Kenya, Zambia, and Zimbabwe), and Australasian (China, Indonesia, Thailand, Australia, New Zealand, and Japan). Overall, 3936 cases of SAH (892 cases in longitudinal studies [9 223 763 person-years of follow-up] and 3044 cases in case-control studies) were available for the analysis, thus allowing 1984 more cases of SAH to be analyzed than in the previous overview.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most longitudinal studies were initiated in the 1970s and were restricted to the US, Japanese, UK, Korean, and Finnish populations. Of the 23 case-control studies, 10 (63% of SAH cases) [12][13][14][15][16][17][18][19][20][21] were population based and 13 hospital based, [22][23][24][25][26][27][28][29][30][31][32][33][34] covering a variety of populations: American (United States), Latin American (Chile, Colombia, Mexico, Brazil, and Jamaica), European (Norway, Germany, Hungary, Portugal, Denmark, Yugoslavia, Slovenia, Finland, and the United Kingdom), African (Kenya, Zambia, and Zimbabwe), and Australasian (China, Indonesia, Thailand, Australia, New Zealand, and Japan). Overall, 3936 cases of SAH (892 cases in longitudinal studies [9 223 763 person-years of follow-up] and 3044 cases in case-control studies) were available for the analysis, thus allowing 1984 more cases of SAH to be analyzed than in the previous overview.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that most risk factors tend to be more hazardous in women than in men, although this difference is statistically nonsignificant, suggests that this may contribute to the higher incidence of SAH observed in women. Case-control 12,14,22,24,26,27 0.7 (0.5-0.8) †Totals represent pooled estimates for all available studies reporting data for both men and women separately or combined; there were a different No. of studies that contributed data to the overall effect estimates and No.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson and the Australasian Cooperative Research on Subarachnoid Hemorrhage Study (ACROSS) Group [24] found a strong positive association between cigarette smoking and SAH, especially for aneurysmal SAH and women, which is virtually eliminated within a few years of smoking cessation. Among patients in Izumo (Japan), hypertension was the most notable risk factor for aneurysmal SAH, regardless of age and sex, followed by cigarette smoking in younger men and hypercholesterolemia in older women.…”
Section: Epidemiology Of Subarachnoid Hemorrhagementioning
confidence: 99%
“…Smoking is an important risk factor for aneurysmal subarachnoid hemorrhage (SAH), and 40-60% of all patients admitted with spontaneous SAH are active cigarette smokers [1][2][3]. Being an active smoker at the time of hospital admission for SAH is a risk factor for the development of delayed cerebral ischemia (DCI) from vasospasm [2,4,5].…”
Section: Introductionmentioning
confidence: 99%